1988
DOI: 10.1192/bjp.152.4.522
|View full text |Cite
|
Sign up to set email alerts
|

Clomipramine, Self-exposure and Therapist-aided Exposure for Obsessive–Compulsive Rituals

Abstract: A randomised treatment design for 49 chronically obsessive-compulsive ritualising patients was devised and three controlled comparisons were made. 1. During 7 weeks of self-exposure instructions, clomipramine treatment improved some measures of rituals and depression significantly more than did placebo medication; this effect was transient and disappeared as drug treatment and exposure were continued for a further 15 weeks. 2. During 11-16 weeks of clomipramine treatment, self-exposure instructions yielded hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
3

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(83 citation statements)
references
References 23 publications
4
76
0
3
Order By: Relevance
“…In another complex study involving self-exposure, clomipramine, and therapist-aided exposure, self-exposure was the most potent; clomipramine played a limited adjuvant role, and therapist-aided exposure a marginal one (Marks et al 1988). A comparison of fluvoxamine with antiexposure, fluvoxamine with exposure, or placebo with exposure was difficult to interpret.…”
Section: )(E)mentioning
confidence: 99%
“…In another complex study involving self-exposure, clomipramine, and therapist-aided exposure, self-exposure was the most potent; clomipramine played a limited adjuvant role, and therapist-aided exposure a marginal one (Marks et al 1988). A comparison of fluvoxamine with antiexposure, fluvoxamine with exposure, or placebo with exposure was difficult to interpret.…”
Section: )(E)mentioning
confidence: 99%
“…Marks and colleagues compared clomipramine and exposure with exposure alone. They found that although clomip ramine initially enhanced the effect of exposure, this drug effect had disappeared at two years' follow-up (Marks et al, 1988).…”
Section: Combining Drugs With Behaviour Therapymentioning
confidence: 99%
“…The recruiting of an informant, such as a close family member, is often very useful in that the OCD sufferer may minimise his level of disability or omit crucial avoidances, and family members may need guidance in avoiding offering reassurance. This often involves explicit coaching, for example, encouraging the relative to respond to requests for reassurance with the same neutral and monotonous response -'the hospital has instructed me to say no answer' (Marks, 1986).…”
Section: Assessment Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy might be warranted also with other psychotherapeutic approaches. Although only one trial reported superiority of combined treatment at the study endpoint [29], in most trials combined treatment was superior to medication or psychotherapy alone in the first weeks [30, 31, 32]. Also, many studies suggest that adding psychotherapy might lead to further improvement in patients who are already stabilised on medication [33, 34, 35, 36].…”
Section: Introductionmentioning
confidence: 99%